Manajemen Peta Jalan (Roadmap) Persandian Pemerintah Daerah Di Indonesia - Pamnungkas, R Wisnu Prio; Khalida, Rakhmi (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The present coding is safeguarding public information, not only guaranteeing security against confidentiality, but on aspects of integrity, authenticity, accessibility, availability and non-denial of information. Security is not only in the password room and is not only done by Sandiman, but more broadly to safeguard ICTs and col-laborate with information security management systems. In order to carry out these functions, it is necessary to make a road map which is a detailed work plan for coding operations. The research method used is descriptive made with reference to Planning, Implementation, Monitoring and Evaluation and Reporting. The results achieved in this study are roadmaps that can be used as a reference for regional governments in the Indonesian territory.